Determination Of Critical Micelle Concentration Of Mixed Solution Of Zwitterionic-Nonionic Surfactants - Mizani Izni, Abdul Muthalib (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Critical micelle concentration (CMC) of zwitterionic surfactant, 3-(N,N-Dimethylmyristylammonio) propanesulfonate (TDAPS) with two types of non ionic surfactant which are Brij 35 and Triton X-IOO have been detennined. The aggregation behavior in mixed system of nonionic-zwitterionic surfactant solution was also studied in this research. Then, the CMC from single and mixed nonionic-zwitterionic surfactant system were compared. Besides, the effect of different concentration of salt solution, sodium chloride (NaCl) to the CMC of mixed nonionic-zwitterionic surfactant solutions was also detennined. Detennination of the CMC value has been perfonned in aqueous phosphate buffer at pH 7.0. From this research, we can conclude that mixed surfactant solution system has a better perfonnance compare to single surfactant and addition of sodium chloride lowered the CMC value of the mixed nonionic-zwitterionic surfactant solution system. UV spectrophotometer was used to check the CMC of single TDAPS, Brij 35 and Triton X-IOO and their mixture. The theory of "Beer's law" has been used to plot at a wavelength of maximum absorbance versus surfactant concentration.